Experiences, barriers and perspectives of midwifery educators, mentors and students implementing the updated emergency obstetric and newborn care-enhanced pre-service midwifery curriculum in Kenya: a nested qualitative study - Duncan N. Shikuku; Sarah Bar-Zeev; Alice Norah Ladur; Helen Allott; Catherine Mwaura; Peter Nandikove; Alphonce Uyara; Edna Tallam; Eunice Ndirangu; Lucy Waweru; Lucy Nyaga; Issak Bashir; et al. (BMC Medical Education, 2024)
Abstract Introduction To achieve quality midwifery education, understanding the experiences of midwifery educators and students in implementing a competency-based pre-service curriculum is critical. This study explored the experiences of and barriers to implementing a pre-service curriculum updated with emergency obstetric and newborn care (EmONC) skills by midwifery educators, students and mentors in Kenya. Methods This was a nested qualitative study within the cluster randomised controlled trial investigating the effectiveness of an EmONC enhanced midwifery curriculum delivered by trained and mentored midwifery educators on the quality of education and student performance in 20 colleges in Kenya. Following the pre-service midwifery curriculum EmONC update, capacity strengthening of educators through training (in both study arms) and additional mentoring of intervention-arm educators was undertaken. Focus group discussions were used to explore the experiences of and barriers to implementing the EmONC-enhanced curriculum by 20 educators and eight mentors. Debrief/feedback sessions with 6–9 students from each of the 20 colleges were conducted and field notes were taken. Data were analysed thematically using Braun and Clarke’s six step criteria. Results Themes identified related to experiences were: (i) relevancy of updated EmONC-enhanced curriculum to improve practice, (ii) training and mentoring valued as continuous professional development opportunities for midwifery educators, (iii) effective teaching and learning strategies acquired – peer teaching (teacher-teacher and student-student), simulation/scenario teaching and effective feedback techniques for effective learning and, (iv) effective collaborations between school/academic institution and hospital/clinical staff promoted effective training/learning. Barriers identified were (i) midwifery faculty shortage and heavy workload vs. high student population, (ii) infrastructure gaps in simulation teaching – inadequate space for simulation and lack of equipment inventory audits for replenishment (iii) inadequate clinical support for students due to inadequate clinical sites for experience, ineffective supervision and mentoring support, lack/shortage of clinical mentors and untrained hospital/clinical staff in EmONC and (iv) limited resources to support effective learning. Conclusion Findings reveal an overwhelmed midwifery faculty and an urgent demand for students support in clinical settings to acquire EmONC competencies for enhanced practice. For quality midwifery education, adequate resources and regulatory/policy directives are needed in midwifery faculty staffing and development. A continuous professional development specific for educators is needed for effective student teaching and learning of a competency-based pre-service curriculum.